Computer Aided Verification 23rd International Conference, CAV 2011, Snowbird, UT, USA, July 14-20, 2011. Proceedings - Gopalakrishnan, Ganesh; Qadeer, Shaz.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 23rd International Conference on Computer Aided Verification, CAV 2011, held in Snowbird, UT, USA, in July 2011.The 35 revised full papers presented together with 20 tool papers were carefully reviewed and selected from 161 submissions. The papers are organized in topical sections on the following workshops: 4th International Workshop on Numerical Software Verification (NSV 2011), 10th International Workshop on Parallel and Distributed Methods in Verifications (PDMC 2011), 4th International Workshop on Exploiting Concurrency Efficiently and Correctly (EC2 2011), Frontiers in Analog Circuit Synthesis and Verification (FAC 2011), International Workshop on Satisfiability Modulo Theories, including SMTCOMP (SMT 2011), 18th International SPIN Workshop on Model Checking of Software (SPIN 2011), Formal Methods for Robotics and Automation (FM-R 2011), and Practical Synthesis for Concurrent Systems (PSY 2011).
Keywords: Computer science; Software engineering; Logic design; Artificial intelligence; Computer Science; Logics and Meanings of Programs; Software Engineering; Programming Languages, Compilers, Interpreters; Mathematical Logic and Formal Languages; Programming Techniques; Artificial Intelligence (incl. Robotics).